ANALISIS PENGGUNAAN INTERNET TERHADAP KARAKTER BERSAHABAT/KOMUNIKATIF PADA PEMBELAJARAN BIOLOGI - Ika Chastanti; Maharani Gultom; Novi Fitriandika Sari (Jurnal Pelita Pendidikan, 2019)
Technological advances that are increasingly rapid have a positive and negative impact on the character of students. One of the negative effects of using the internet is that it is reduced to the ability to communicate / communicate with students in daily life. Students prefer to access social media rather than having to communicate directly with those around them. The purpose of this study is to find out the internet usage among students towards communicative / communicative character in biology learning . This study is a qualitative study in which in-depth interviews are the main data source, and questionnaires as secondary data sources. The sampling technique used is Purposive sampling. The samples from this study were high school students and Biology teachers. The results of the study show that friendly characters / if communicities have not been well established (28.89%) students answer sometimes. The role of the teacher is also not maximal in instilling friendly / communicative characters. Teachers also prefer to access the internet when the biology learning process takes place. The cultivation of friendly / communicative character values requires the role of parents. The role of parents is also not maximal to shape character when students are at home. Parents allow students to access the internet and there is no time limit in their use so that direct communication between parents and students is not well established.Technological advances that are increasingly rapid have a positive and negative impact on the character of students. One of the negative effects of using the internet is that it is reduced to the ability to communicate / communicate with students in daily life. Students prefer to access social media rather than having to communicate directly with those around them. The purpose of this study is to find out the internet usage among students towards communicative / communicative character in biology learning . This study is a qualitative study in which in-depth interviews are the main data source, and questionnaires as secondary data sources. The sampling technique used is Purposive sampling. The samples from this study were high school students and Biology teachers. The results of the study show that friendly characters / if communicities have not been well established (28.89%) students answer sometimes. The role of the teacher is also not maximal in instilling friendly / communicative characters. Teachers also prefer to access the internet when the biology learning process takes place. The cultivation of friendly / communicative character values requires the role of parents. The role of parents is also not maximal to shape character when students are at home. Parents allow students to access the internet and there is no time limit in their use so that direct communication between parents and students is not well established.